THE ESSENCE OF THE CONCEPTS OF TERRORISM AND EXTREMISM - Nurdinov Javharbek Bahromjonovich (Scholar Express Journal, 2024)
This article states that in the context of globalization and the ongoing transformation of international and regional conflicts, the issue of effectively combating extremism and terrorism has become one of the topical topics on the agenda. Therefore, in the current complex situation, protecting the population, especially young people, from the ideas of terrorism that promote violence and brutality is becoming more and more important. It becomes an important task to inculcate healthy ideology and constructive ideas in the minds of the members of the society so that the fight against it gives positive results
Keywords: Terrorism; extremism; Religious extremism